Kerentanan Seismik di Wilayah Telanaipura dan Kotabaru Kota Jambi - Hidayat, Rizki; Kusmita, Tri (Jurusan Fisika, Universitas Bangka Belitung, 2020)
Geologically the city of Jambi lies in the formation of Air Benakat, Muara Enim, Kasai, and alluvium deposits. The rock units that make up this formation were all composed by fine sediment. Based on these geological conditions, the Jambi City region has a high level of seismic priority. This research was conducted to study seismic vulnerability in this region, using the microtremor method. Microtremor is a ground vibration that can be produced by natural resources. This natural resource consists of wind and sea waves that have a long period of time or like traffic, factory machinery, and so on. Based on the results of the study obtained from the Kotabaru and Telanaipura regions have natural frequencies in the range 1.24 Hz - 4.35 Hz. The amplification factor was 1.13 - 3.34 and it was included in the low category. seismic vulnerability index in both regions was 0.50 - 8.58 x 10-6 cm / s2. seismic vulnerability index values were relatively high in Kelurahan Penyengat Rendah (Telanaipura). It was not recommended for skyscraper construction.